Malaria and malnutrition in children under the Seasonal Malaria Chemoprevention (SMC) coverage in the health district of Nanoro, Burkina Faso - Eulalie Wendingouda Compaore; Paul Sondo; Berenger Kabore; Toussaint Rouamba; Amélé Fifi Chantal Kouevi; Ipéné Mylène Carenne Bayala; Sié A. Elisée Kambou; Kié Solange Millogo; Ismaïla Bouda; Delwendé Florence Ouedraogo; So-vii Franck Hien; Adama Kazienga; et al. (PLoS ONE, 2026)
Introduction Malaria and malnutrition are major causes of childhood morbidity and mortality. Most of children receiving Seasonal malaria chemoprevention (SMC) are also generally malnourished during SMC delivery period. This study aimed at assessing the risk of malaria infection in malnourished children, compared to children with an adequate nutritional status (ANS) during the delivery period of SMC intervention in the health district of Nanoro, Burkina Faso. Methods A longitudinal survey of children aged 6–59 months receiving SMC intervention was carried out between 2020 and 2022 in Nanoro, Burkina Faso. WHO online anthro survey tool was used to assess the nutritional status. Included children were stratified into two sub-groups as malnourished from the start of the first SMC round until one month after the last SMC round and those of ANS during that same period. In addition to the monthly home visits, all health care attendance were recorded for all participants. At each visit, socio-anthropometric data were collected. Blood smears were collected for malaria diagnosis by rapid diagnostic test (RDT) and microscopy. The effect of the nutritional status on the occurrence of uncomplicated malaria was assessed using a negative binomial model, with results expressed as incidence risk ratio (IRR). Results Out of the 425 children included this study, 260 were malnourished, while 165 children had an ANS. Malaria incidence per 1000 child-month were higher in undernutrition (974.47) than in ANS (214.47). Malnourished children were 1.41 times more likely to have t an episode of clinical malaria than children with ANS (IRR 1.42; 95% CI 1.03–1.94; p = 0.028). Conclusion There was an increased risk of malaria infection in undernourished children compared to children with an adequate nutritional status suggesting the need of combining SMC intervention with nutrients supplementation to achieve best impact for malaria control in food insecure areas.